Dubious effect of the high biventricular paced beats percentage itself on the cardiac resynchronization efficacy in patients with atrial fibrillation. The randomized Pilot-CRAfT Study results. (19th May 2022) - Ciszewski, JB; Tajstra, M; Kowalik, I; Maciag, A; Zajac, D; Pytkowski, M; Gasior, M; Sterlinski, M
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institute of Cardiology statutory grant Background: The presence of atrial fibrillation (AF) in cardiac resynchronization therapy (CRT) recipients is common and AF is a marker of poorer CRT response. The negative influence of AF on CRT efficacy is belived to be mediated mainly by the drop of effectively captured biventricular paced beats percentage (BiVp%). According to observational trials, the minimal BiVp associated with better outcomes is 95-98%, however there is lack of randomized trials to confirm this findings. Purpose: The purpose of the study was to assess the influence of BiVp% itself on the clinical outcomes in the population CRT patients with atrial fibrillation in a prospective, randomized cohort. Methods: The study included the prospective Pilot-CRAfT study participants that is patients with CRT and permanent or persistent AF lasting for ≥6 months that were randomly assigned to rhythm or rate control strategy. We divided the whole study population according to their BiVp at the 12 month follow-up with two borderline BiVp values (BiVp >98% vs <98% and >95% vs <95%) and analysed the echocardiographic indices, exercise tolerance and quality of life between the prespecified groups. Results: The study included 43 CRT patients (97, 7% males) aged 68, 4 (SD: ±8, 3) years with mean BiVp% 82, 4% ±9, 7% at baseline. The mean baseline left ventricular ejection fraction (LVEF), left ventricular end diastolic diameter (LVEDD) and maximal oxygen uptake (VO2max) were: 30 ±8%, 65 ±8 mm, 14 ±5 mL/(kg*min), respectively. In both of the study arms the BiVp% raised significantly reaching 98, 1 ±2, 3% and 96, 3 ±3, 9% in the rhythm control and the rate control arms respectively (P=0, 093). As a result the were overall 21 patients with BiVp >98% and 29 patients with BiVp >95% at the end of the study. The BiVp groups >98% vs <98% and >95% vs <95% did not differ as to baseline characteristics and we have not observed any differences in the mean LVEF, mean LVEDD, mean VO2max, and quality of life in the prespecified BiVp% groups at the end of the follow up. Moreover no linear correlations between the BiVp% and LVEF, LVEDD, VO2max values were observed. However, in the rate control group patients with AVNA performed had lower LVEDD at the end of the study (57, 7 ±3, 0 vs 65, 4 ±7, 0 p=0, 007) and significant decrease in the LVEDD after AVNA was observed (-8, 6 95%CI [-14, 9; -2, 3]). Conclusions: The BiVp >98% or >95% alone does not seem to warrant good response to cardiac resynchronization in patients with persistent atrial fibrillation as assessed in the prospective randomized cohort. However, performing AVNA in this group of patients may be beneficial in terms of LVEDD decrease.